Magnesium status modulating the effect of serum vitamin D levels on retinopathy: National Health and Nutrition Examination Survey 2005 to 2008 - Xu, Lei; Yuan, Penghua; Liu, Wanrong; Liu, Linlin; Li, Xiongfeng; Xie, Lianfeng (Frontiers in Nutrition, 2024)
Aim: Magnesium levels may influence the effect of vitamin D levels on the body. This study aimed to assess the combined effect of magnesium status as reflected by magnesium depletion score (MDS) and vitamin D status on the risk of retinopathy. Methods: This cross-sectional study included participants aged 40 years and older with complete information on vitamin D, MDS, and retinopathy assessment from the 2005-2008 National Health and Nutrition Examination Survey (NHANES). Logistic regression analysis was utilized to analyze the relationship of MDS and vitamin D with retinopathy and expressed as odds ratio (OR) and 95% confidence interval (CI). Results: Of these 4,953 participants included, 602 (9.53%) participants had retinopathy. Serum vitamin D levels ≤30 nmol/L (vs. >30 nmol/L) (OR=1.38, 95%CI: 1.05-1.81) and MDS >2 points (vs. ≤2 points) (OR=1.47, 95%CI: 1.01-2.16) were associated with higher odds of retinopathy. There was an interaction between MDS and vitamin D on the increased odds of retinopathy [OR=2.29, 95%CI: 1.12-4.68), Pinteraction=0.025]. In different MDS groups, serum vitamin D levels ≤30 nmol/L increased the odds of retinopathy only in the MDS >2 group (OR=2.90, 95%CI: 1.16-7.24), but not in the MDS ≤2 group (P=0.293). Subgroups analyses demonstrated that the interaction between MDS and serum vitamin D on retinopathy was observed in males (OR=6.88, 95%CI: 1.41-33.66, Pinteraction=0.019), people with diabetes (OR=3.43, 95%CI: 1.78-6.63, Pinteraction<0.001), and people with body mass index (BMI) ≥25kg/m2 (OR=2.46, 95%CI: 1.11-5.44, Pinteraction=0.028). Conclusion: Magnesium plays a moderating role in the relationship between serum vitamin D and retinopathy. The protective effect of vitamin D against retinopathy was primarily present among those with inadequate magnesium levels.